Analysis of The Commentaries on Sunan At-Tirmidhi - Abdusattorov Ilhom Bakhriddinovich (Jurnal Studi Ilmu Alquran dan Tafsir, 2025)
In this article, various commentaries written in different periods on the work Sunan at-Tirmidhi by the eminent hadith scholar Abu Isa Muhammad ibn Isa at-Tirmidhi are analyzed. Moreover, the study examines, on a scholarly basis, the earliest commentaries as well as later annotations and glosses authored by scholars belonging to the Hanafi school and other legal traditions. The research focuses on the distinctive features of these commentaries, their methodological aspects, and their contribution to the development of hadith studies. This work suffices to as an important source of gaining a deeper understanding of the scholarly heritage related to Sunan at-Tirmidhi, and exploring the interaction among various schools and approaches within the science of hadith